Numerical Simulation on Hydrofracture Propagation in Fractured-Vuggy Unconventional Reservoirs - Tingxue Jiang; Haitao Wang; Xiaobing Bian; Daobing Wang; Jun Zhou; Bo Yu (Geofluids)
The unconventional reservoirs such as carbonate formation develops complex and diverse storage space structures, and it is composed of large-scale cavity, dissolved vug, and fractures. The carbonate reservoir is highly heterogeneous. Acid fracturing of carbonate reservoir is completed through the complex mechanical mechanism of interaction between vug and hydraulic fracture (HF). We use the equivalent method of reducing the rock strength by acid etching and serious fluid leakoff during interaction of HF and vug to establish a finite element (FE) model of HF propagation during acid fracturing in the fractured-vuggy carbonate reservoir. The model considers the effect of serious fluid leakoff during interaction between HF and vug, mechanism of interaction between HFs and the fracture-vug system, and change in acid etching intensity. Then, we carry out numerical simulation on impacts of injection rate, fluid viscosity, leakoff behavior in fractures and vugs, and natural fracture (NF) approaching angle on HF propagation in acid fracturing and compare the characteristics of injection pressure, fracture pressure, and HF size. It is suggested that the acid fracturing treatment should be operated by increasing the acid solution viscosity to reduce fluid leakoff, injecting fracturing fluid and acid fluid alternatively, increasing injection rate, and injecting fibers and ceramics when small pressure drop occurs during the HF interacts with the fracture-vug. When a large pressure drop occurs, it is suggested that the middle-low viscosity acid be injected at a low rate to etch the carbonate rock and enhance the fracture conductivity. HF propagates under higher pressure when the NF approaching angle is smaller.